Exosomal long noncoding RNA HOTTIP as potential novel diagnostic and prognostic biomarker test for gastric cancer - Zhao, Rui; Zhang, Yanli; Zhang, Xin; Yang, Yongmei; Zheng, Xin; Li, Xiaohui; Liu, Yingjie; Zhang, Yi (Molecular cancer, 2018)
Long noncoding RNA HOTTIP plays important roles in the generation and progression of human cancers. Exosomes participate in cellular communication by transmitting moleculars between cells and are regarded as suitable candidates for non-invasive diagnosis. However, the existence of HOTTIP in the circulating exosomes and the potential roles of exosomal HOTTIP in gastric cancer (GC) was poorly understood. This study aims at investigating the clinical roles of exosomal HOTTIP in GC. Serum exosomal HOTTIP from 246 subjects (126 GC patients and 120 healthy people) were detected by reverse transcription real-time quantitative polymerase chain reaction (RT-qPCR). Our results showed that expression levels of exosomal HOTTIP were typically upregulated in GC than in normal control (P < 0.001). And its expression levels were significantly correlated with invasion depth (P = 0.0298) and TNM stage (P < 0.001). The AUC for exosomal HOTTIP was 0.827, which demonstrated a higher diagnostic capability than CEA, CA 19-9 and CA72-4 (AUC = 0.653, 0.685 and 0.639, respectively) (P < 0.001). The Kaplan-Meier analysis showed a correlation between increased exosomal HOTTIP levels and poor overall survival (OS) (logrank P < 0.001). And univariate and multivariate COX analysis revealed exosomal HOTTIP overexpression was an independent prognostic factor in GC patients (P = 0.027). These findings demonstrated that exosomal HOTTIP may be a potential biomarker for GC in diagnosis and prognosis.